2022
DOI: 10.1002/cam4.5175
|View full text |Cite
|
Sign up to set email alerts
|

Association of raloxifene and tamoxifen therapy with cognitive performance, odds of mild cognitive impairment, and brain MRI markers of neurodegeneration

Abstract: The aim of this cross‐sectional study was to examine whether a history of selective estrogen receptor modifiers (SERMs), tamoxifen and raloxifene, use was associated with cognitive performance, odds of mild cognitive impairment (MCI), or magnetic resonance imaging (MRI) markers of neurodegeneration associated with Alzheimer's disease. We included women with prior history of breast cancer or no prior history of any cancer at enrollment in the Mayo Clinic Study of Aging (MCSA). This information was abstracted us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Among these SERMs, tamoxifen, commonly used for adjuvant therapy for early breast cancer treatment, is able to cross the blood–brain barrier, and with its well-documented safety profile, has been of interest for clinical use in remyelination. However, studies on cognition and tamoxifen in the non-MS population have shown inconsistent results; this heterogeneity may be partially attributed to differing age groups, bucketing of hormonal therapies, and uses of non-breast cancer controls vs. breast cancer controls [ 65 •]. Some studies indicate associations with tamoxifen and impaired verbal learning and memory [ 66 ] and higher risk of Alzheimer’s disease [ 67 ], while others, including a large retrospective cohort study of 57,843 women aged 45 to 90 with breast cancer, reported lower risk of Alzheimer’s disease and dementia after tamoxifen use [ 68 ].…”
Section: Selective Estrogen and Androgen Receptor Modulators (Serm An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Among these SERMs, tamoxifen, commonly used for adjuvant therapy for early breast cancer treatment, is able to cross the blood–brain barrier, and with its well-documented safety profile, has been of interest for clinical use in remyelination. However, studies on cognition and tamoxifen in the non-MS population have shown inconsistent results; this heterogeneity may be partially attributed to differing age groups, bucketing of hormonal therapies, and uses of non-breast cancer controls vs. breast cancer controls [ 65 •]. Some studies indicate associations with tamoxifen and impaired verbal learning and memory [ 66 ] and higher risk of Alzheimer’s disease [ 67 ], while others, including a large retrospective cohort study of 57,843 women aged 45 to 90 with breast cancer, reported lower risk of Alzheimer’s disease and dementia after tamoxifen use [ 68 ].…”
Section: Selective Estrogen and Androgen Receptor Modulators (Serm An...mentioning
confidence: 99%
“…Some studies indicate associations with tamoxifen and impaired verbal learning and memory [ 66 ] and higher risk of Alzheimer’s disease [ 67 ], while others, including a large retrospective cohort study of 57,843 women aged 45 to 90 with breast cancer, reported lower risk of Alzheimer’s disease and dementia after tamoxifen use [ 68 ]. Yet, others show no association between tamoxifen and cognition [ 65 •].…”
Section: Selective Estrogen and Androgen Receptor Modulators (Serm An...mentioning
confidence: 99%
“…However, there are scattered reports from retrospective studies regarding the oral administration of raloxifene and its impact on cognitive function. Some studies suggest that it preserves cognitive function [ 16 ], while others indicate that it has no effect [ 17 ]. Recently, large-scale clinical trials were conducted in patients with mild cognitive impairment and AD, and the results demonstrated that raloxifene was not effective in preventing the onset of AD [ 18 ].…”
Section: Introductionmentioning
confidence: 99%